The behaviour of tungsten oxide on phosphor-tellurite glasses for photon proton and alpha particles shielding - Ravangvong, Sunantasak; Glumglomchit, Punsak; Pranudomrat, Kunlanun; Muangsri, Latthaphon; Lertlimpiyarat, Paramee; Supakom, Amonwan; Sriwongsa, Kittisak; Glumglomjit, Sakchai; Wattana, Wanna (Indochina Applied Sciences, 2023)
This research, photons shielding properties such as mass attenuation coefficients (mm), effective atomic number (Zeff), effective electron density (Nel) and kinetic energy per unit mass (kerma) relative to air for WO3 based on TeO2–P2O5–WO3 glass system have been simulated by WinXCom software program at energies of 10–3–105 MeV. Also, buildup factors (BFs) have been estimated at widely energy ranging 15 keV – 15 MeV for penetration depths (PD) until 40 mean free path (mfp). The results of glass system in formula (70–x) TeO2–30P2O5–xWO3 at x = 10, 20, 30, 40, and 50 mol% exhibited that the partial replacement of TeO2 by WO3 was adjusted photons attenuation behaviors for get better. In addition, mass sopping power (MSP) and projected range (PR) were evaluated using SRIM software program for proton (H+1) and alpha particles (He+2) at kinetic energy ranging 10 keV – 10 MeV. The results may be inferred that glass sample with high WO3 content was superb for photons, proton and alpha particles attenuation. The results of this research may be useful in enhancing optimization and potential to use as a transparent material to against photon, proton and alpha particles.